Genetic Exceptionalism & Legislative Pragmatism - Rothstein, Mark A. (The Hastings Center report, 2005)
Can passing antidiscrimination laws ever be a bad idea? Yes, if broad policy reform is abandoned in favor of genetic-specific legislation. But in spite of its serious flaws, both in concept and in practice, genetic-specific legislation is sometimes worth passing anyway.